2002
DOI: 10.1042/bst0300916
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between protein allergens and model gastric emulsions

Abstract: T h e observed resistance to pepsinolysis of known food allergens has been suggested as a predictor of their allergenic risk. Consequently, resistance to pepsinolysis has become incorporated into decision tree assessment for potential allergenic risk posed by novel foods. However, existing methods take little account of the interaction between food structure and physiological conditions existing during digestion in aivo. Here we show that a range of protein allergens can adsorb to model stomach emulsions, prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Although, according to Burnett et al (2002), BS exert a solubilising effect, removing proteins adsorbed to emulsions and favouring their resolubilisation in aqueous phases, our results show that it is likely that LYS precipitates in the duodenum at pH values, BS and PC concentrations representative of a fed state and, to a lesser extent, of a fasted state. In fact, when LYS is administered orally to human patients (as used for the treatment of chronic sinusitis and to promote expectoration in the case of respiratory disease), food intake negatively affects the uptake of the enzyme, with the maximum levels detected being almost 10-fold lower than those after an identical dose taken after an overnight fast (Hashida, Ishikawa, Nakamichi, & Sekino, 2002).…”
Section: Effect Of the Presence Of Bs And Pc On The Duodenal Digestiomentioning
confidence: 57%
“…Although, according to Burnett et al (2002), BS exert a solubilising effect, removing proteins adsorbed to emulsions and favouring their resolubilisation in aqueous phases, our results show that it is likely that LYS precipitates in the duodenum at pH values, BS and PC concentrations representative of a fed state and, to a lesser extent, of a fasted state. In fact, when LYS is administered orally to human patients (as used for the treatment of chronic sinusitis and to promote expectoration in the case of respiratory disease), food intake negatively affects the uptake of the enzyme, with the maximum levels detected being almost 10-fold lower than those after an identical dose taken after an overnight fast (Hashida, Ishikawa, Nakamichi, & Sekino, 2002).…”
Section: Effect Of the Presence Of Bs And Pc On The Duodenal Digestiomentioning
confidence: 57%
“…Burnett et al [22] published data on the behaviour of a range of protein allergens in the presence of model emulsion systems under simulated gastric and simulated duodenal conditions. A number of major allergens were found to adsorb to model stomach emulsions and subsequently desorb when duodenal conditions prevailed.…”
Section: Incorporation Of Gut Lipid Phasesmentioning
confidence: 99%
“…Decreased digestibility through adsorption would also help explain why proteins readily susceptible to pepsin digestion, like BSA, can be identified as food allergens. Furthermore, fluorescence and FTIR spectroscopy studies have shown that proteins adsorbed to oil/water interfaces can be partly denatured [22]. This is a recognised phenomenon associated with protein adsorption to oil/water interfaces [24].…”
Section: Incorporation Of Gut Lipid Phasesmentioning
confidence: 99%
“…The demonstration of an acid-induced molten state in SKTI assumes importance because this conformation is commonly involved in translocation of proteins across membrane barriers and even in membrane insertion [34]. The ability of a food protein to be an allergen may be related to its stability in the acid environment of the digestive system by assuming a more molten structure, which is also able to cross the gastrointestinal membrane barrier and thereby initiate the IgE response [34,35].…”
Section: Discussionmentioning
confidence: 99%